The Architecture of Policy Transfer - Legrand, Tim. author. aut Link
XXXV, 232 p. 3 illus.
Keywords: This book investigates the increasing circulation and transfer of public policy ideas between the UK, US and Australia since the 1990s. It argues that the upsurge in policy transfer amongst and between these states can be explained by a structural and shared commitment between these states to a distinctive institutional ideology of policy-making. This ideology, it is claimed, is partly a product of the historical proximity of ‘Anglosphere’ states, and in recent years can be traced through the evolution of New Public Management principles through to Third Way communitarianism. Tim Legrand is Associate Professor of International Studies at the University of Adelaide, Australia, adjunct Associate Professor at the University of Canberra, Australia, and adjunct Research Fellow of the National Security College at the Australia National University. He has previously held research and lecturing positions at the Australian National University and Griffith University, Queensland, Australia. His research is concerned with the transnational dimensions of public policy, with a particular concern with the networked security communities of the Anglosphere and the politics of security. He is the co-author of Banning Them, Securing Us? (with Lee Jarvis) and his research has been published in leading international journals including Public Administration, Political Studies, Review of International Studies, Security Dialogue, Policy Studies, British Politics, European Political Science, and the Journal of Comparative Policy Analysis.